123k views
1 vote
Which pair shows equivalent expressions? 3 (x + 2) = 3 x + 6 3 x + 2 x = x squared (3 + 2) 3 x + 2 = 3 (x + 2) Negative 3 (2 + x) = negative 6 x minus 3

User Bartop
by
5.3k points

2 Answers

5 votes

Answer: the answer is a.3 (x + 2) =

Step-by-step explanation: because when opening the equation u multiply 3 times x and 3 times 2 so the final aswer is 3x+6

User Jastend
by
6.6k points
5 votes

Answer:

The first pair shows equivalent expressions.

Explanation:

3(x+2), you would have to distribute 3 among x and 2, also known as expanding the expression. So you'd do 3*x + 3*2, which equals 3x+6

The first equation is 3(x+2)=3x+6

Therefore, the first pair shows equivalent expressions.

User Bald Bcs Of IT
by
6.4k points